(untitled) (SAARC Journal of Agriculture, 2015)
The present study was aimed to investigate the dietary effect of different levels of turmeric (Curcuma longa) powder on the performance of broiler during summer (June-July), 2013. Four experimental rations designated as T0, T1, T2 and T3 having 0%, 0.5%, 1.0% and 1.5% Turmeric (Curcuma longa) powder were fed to 120 broiler chicks (Ross 308), randomly distributed into 12 replicates, so as to have 3 replicates per treatment and 10 chicks per replicate. Average weight gain, feed consumption, feed efficiency, dressing yield and survivability were used as criteria of response to feeding turmeric powder. Organs weight including heart, liver and gizzard were also recorded. The mean body weight gain and average feed efficiency (feed gain-1) per broiler significantly increased (P<0.01) by turmeric supplemented feed compared to control feed. The average feed consumption and survivability of broiler chick non- significantly (P>0.05) improved due to by turmeric supplementation in the diets. Inclusion of turmeric powder caused slightly increased the carcass traits of broiler chicks i.e., average weight of liver, heart and gizzard but the differences were non-significant (P>0.05). A significant decrease (P<0.01) in abdominal fat pad and significant increase (P<0.05) in dressing yield was observed in chickens fed the turmeric supplemented diets. The results of the present study suggest that the use of turmeric (Curcuma longa) powder as feed additive at a level of 0.5% enhances the growth performances and carcass yield of broiler chicks. SAARC J. Agri., 13(1): 188-199 (2015)